DEVELOPING ANIMATION VIDEOS AND GAME CARDS FOR TEACHING TELLING TIME IN ENGLISH TO FOURTH-GRADE STUDENTS - Kurniawati, Ike; Widagdo, Arif (English Review: Journal of English Education, 2025)
Changes in the curriculum in education affect how the implementation of existing learning, as well as in learning media, is needed as an effort to stimulate students' abilities in the learning process to be more effective and efficient. The purpose of this research is to develop animation video media and game cards on Telling Time material in English. This research uses the type of research and development with the ADDIE model. The research subjects were fourth grade students of Wates 01 Semarang State Elementary School. Data collection techniques used in this research are (1) interview; (2) observation; (3) questionnaire; (4) test; and (5) documentation. The instruments used are interview guides, documentation, needs questionnaires, media response questionnaires, pretest and posttest questions, and validation sheets conducted by 2 experts, namely media experts, material experts, and language experts. Data analysis techniques were carried out by normality test (Shapiro-Wilk), t test, and n-gain test. The results showed that animated video media and playing cards can improve student understanding and student learning outcomes in English. This result is evidenced from the average value on students there is an increase in small-scale learning outcomes pretest average value 58.3 and posttest average 86.8 then on a large scale pretest average value 57 and posttest average value 82.8. Then the results of the N-gain test on a small scale of 0.7512 and a large scale of 0.5925 which means the high and medium categories, can be concluded to be effective for use in learning. Therefore, it can be concluded that animation video media and game cards can be said to be a category worth using in an interesting learning process and can improve student understanding and learning outcomes.